Management of Hydrocephalus in Congenital Toxoplasmosis using Pyrimethamine and Sulfonamide: A Systematic Review - Waicus, Sarah; Vrbanic, Lauren (Trinity Student Medical Journal, 2022)
Background: Congenital toxoplasmosis is a serious disease that occurs when the foetus is infected with the parasite. Toxoplasma gondii. A consequence of vertical transmission from mother to foetus is hydrocephalus. This is classified as an increase in intracranial pressure causing swelling of the brain. It is unknown whether the current gold standard of antibiotic treatment of pyrimethamine and sulfonamide is adequate. The objective of this review is to compare the efficacy of pyrimethamine and sulfonamide treatment duration in managing hydrocephalus induced by congenital toxoplasmosis. Methods: A systematic review was conducted by two independent reviewers across several medical databases including Ovid MEDLINE, Cochrane Central and EMBASE. Seven articles including case reports, retrospective cohorts, randomised controlled trials, longitudinal studies, and systematic reviews met the inclusion criteria. Infants were classified from birth to 24 weeks old. Results: There was a lack of conclusive evidence regarding the efficacy and safety of pyrimethamine and sulfonamide. Multiple studies revealed pyrimethamine and sulfonamide were effective in reducing infant deformities and neurological conditions, only when rapidly administered after birth. However, contradicting evidence revealed pyrimethamine and sulfonamide had no significant effect on hydrocephalus. Conclusion: Novel pharmaceutical interventions for managing hydrocephalus caused by congenital toxoplasmosis are needed, as the existing treatments are inadequate. Since treatment options have dwindled in the last decade, toxoplasmosis is classified as a neglected parasitic infection. Renewed interest in conducting higher-quality trials is required to elucidate different therapeutic interventions for clinical use.